Complex Regional Pain Syndrome - Prevention, diagnosis and treatment - Aleksandra Mazurek; Katarzyna Cyboran; Monika Kuc; Dominik Machaj; Damian Machaj (Kazimierz Wielki University, 2022)
CRPS different from other chronic pain conditions by the presence of signs indicating autonomic and inflammatory changes in the area of ​​pain.[4]Otherwise called Sudeck syndrome, it is characterized by pain and swelling of the affected limb, and in the final stage - contractures in the joints. The skin becomes dry and trophically changed. If the cause of the symptoms is known, causal treatment is used, if not - the following attempts are made to treat this syndrome.The pathophysiology of CRPS is unknown, so diagnostic tests are used to rule out a pathology other thanComplex Regional PainSyndrome.The average age of onset is 42 years. Statistically, women suffer from the disease three times more often than men. [7]